Microscopic examination using negative staining for rapid diagnosis of syphilis - Rosana, Yeva; Effendi, Ida; Indriatmi, Wresti; Yasmon, Andi (Universa Medicina, 2022)
BACKGROUNDSyphilis is a global health problem, especially in developing countries including Indonesia. Treponema pallidum, the etiologic agent of syphilis, cannot be cultured in vitro. Syphilis has several clinical manifestations, making laboratory testing a very important aspect of diagnosis. Microscopic examination may support the diagnosis but is rarely used in Indonesia. The aim of this study was to evaluate negative staining using the light microscope to detect T. pallidum in syphilitic lesions. METHODSA cross-sectional study was conducted involving 27 subjects who came to several dermato-venereology clinics in Jakarta. Exudates were collected from genital ulcers, condylomata lata, and dry mucocutaneous rash on palms and soles of syphilis patients. Negative staining using one drop of Indian ink was used to examine for treponemas under the light microscope at 10x100 magnification. RESULTSMicroscopic examination using negative staining showed a few clusters of small and spiral shaped bacteria. Of the 39 specimens from 27 subjects, microscopic examinations were successfully done on 10 specimens. Observations could only be conducted on 5 specimens, 3 (60.0%) of which showed the morphology of spirochetes. This examination is the easiest method for detecting the bacteria. Moreover, the bacteria that were isolated from painless genital ulcers could be observed more clearly than those from erythematous maculopapular lesions. CONCLUSIONTreponema pallidum was successfully detected by microscopic examination in all moist lesions, but was difficult to detect in dry lesions. Negative staining under the light microscope appears to be simple, affordable, and available in most microbiology laboratories in Indonesia.